Association Between the Concentration and Rangeability of Cystatin C and Mortality of COVID-19 Patients With or Without Type 2 Diabetes Mellitus: A Retrospective Analysis - Yang, Lei; Xu, Dou; Tan, Yiqing; Li, Bolin; Zhu, Dan; Wang, Jingbo; Sun, Hui; Liu, Xinglong; Zheng, Xiaopu; Zhu, Ling; Li, Zhongyu (Frontiers in Endocrinology, 2021)
Background: We investigated if the concentration and “rangeability” of cystatin C (CysC) influenced the prognosis of coronavirus disease 2019 (COVID-19) patients suffering from, or not suffering from, type-2 diabetes mellitus (T2DM). Methods: A total of 675 T2DM patients and 572 non-T2DM patients were divided into “low” and “high” CysC groups and low and high CysC-rangeability groups according to the serum CysC level and range of change of the CysC level, respectively. Demographic characteristics, clinical data and laboratory results of the four groups were analyzed. Results: COVID-19 patients with a high level and rangeability of CysC had more organ damage and higher risk of death compared with those with a low level or low rangeability of CysC. Patients with a higher level and rangeability of CysC had more blood lymphocytes and higher levels of C-reactive protein, alanine aminotransferase, and aspartate aminotransferase. After adjustment for possible confounders, multivariate analysis revealed that CysC >0.93 mg/dL were significantly associated with the risk of heart failure (OR = 2.231, 95% CI: 1.125–5.312) and all-cause death (2.694, 1.161–6.252). CysC rangeability >0 was significantly associated with all-cause death (OR = 4.217, 95% CI: 1.953–9.106). These associations were stronger in patients suffering from T2DM than in those not suffering from T2DM. Conclusions: The level and rangeability of CysC may influence the prognosis of COVID-19. Special care and appropriate intervention should be undertaken in COVID-19 patients with an increased CysC level during hospitalization and follow-up, especially for those with T2DM.